Determinan Tax Morale Pada Wajib Pajak Orang Pribadi Non Karyawan(Studi Empiris Pada Wajib Pajak Orang Pribadi Non Karyawan Yang Terdaftar Di Kantor Pelayanan Pajak Tampan Kota Pekanbaru) - Hariko Wayra; Dwi Fionasari (P3M Politeknik Negeri Bengkalis, 2025)
The purpose of this study is to analyze the determinants of tax morale in non-employee individual taxpayers using the Theory of Planned Behavior approach with a focus on factors that are predicted to be the main constituents of tax compliance. This study is a quantitative study with a population of 117,310 non-employee individual taxpayers registered at the Pekanbaru Tampan Pratama Tax Office and this study was conducted in December 2024 involving 100 respondents as a sample. The analysis technique used is random sampling and multiple linear regression analysis. The results of this study indicate that the variables Trust In The Government (X1), Personal Interest (X2) and Perception Of Justice (X3) have a significant effect on Tax Morale (Y). The results of this study are expected to provide benefits for policy makers and tax authorities in improving the tax morale of non-employee taxpayers because non-employee taxpayers have a greater tax reporting, so this study helps to understand the factors that influence their tax morale more specifically.